Korelasi Antara Dukungan Sosial Orang Tua dan Self‐Directed Learning pada Siswa SMA - - Tarmidi; Ade Riza Rahma Rambe (Jurnal Psikologi, 2010)
The purpose of this research was to examine the relationship between parental social support and self direction in learning on highschool students. The population of this research was the students of SMA Negeri 1 Medan, and a sample of 195 students was recruited from the 10 th grade, the 11 th grade, and the 12 th grade. The researcher used a set of two Likert scales, including Self Directed Learning Scale, which was designed according to the components of self direction in learning by Candy (1991), and Parental Social Support Scale, which was designed based on the dimensions of social support by Sarafino (2002). The Parental Social Support Scale consists of 50 items, and the reliability of the scale is r=0.960. The Self Directed Learning Scale consists of 50 items, and the reliability of the scale is r=0.940. To analyze the result, the researcher used Pearson Product Moment Coefficient Correlation. Outcome of data analysis shows there is significant correlation between parental social support and self direction in learning. The results showed a positive correlation between parental social support and self direction in learning on highschool students (r = 0.477; ρ <0,05). It indicated that the higher the parental social support, the higher the self direction in learning and conversely the lower the social support of parents the lower the self direction in learning.